Administration of fiscal regimes for petroleum exploration and development - Gara, John (UN New YorkUS, 1995)
Provides an analysis of the issues and options which are crucial to the formulation of fiscal regimes for petroleum exploration and development in the context of a realistic assessment of the consequent administrative requirements.